2022
DOI: 10.1021/jacs.2c09556
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Open-[60]Fullerene Ligands with Giant Dissymmetry Factors

Abstract: The optical resolution of open-[60]­fullerenes has been limited to only one example since 1998, while the recent advances revealed the excellence of fullerenes as revisited chiral functional materials. Different from conventional chiral induction on [60]­fullerene by a multiple-functionalization, a random disruption of the spherical π-conjugation is avoidable for open-[60]­fullerenes. Moreover, the macrocyclic orifices enable a metal coordination which endows modulated electronic structures on chiral chromopho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 55 publications
(32 reference statements)
0
12
1
Order By: Relevance
“…At around the same time, Fuchter and co‐workers found that bis(methano)[60]fullerenes show a fast and high photocurrent response in CPL‐detecting devices [17] . Very recently, we reported a high dissymmetry factor of g abs =±0.20 at 710 nm for an open [60]fullerene [18] . Under these circumstances, we thus focused on the synthesis of donor–acceptor type chiral open [60]fullerenes targeted toward a broadband CD activity up to NIR region, in which the effective orbital hybridization with the donor units potentially renders low‐energy transitions electric dipole‐allowed [19, 20] .…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…At around the same time, Fuchter and co‐workers found that bis(methano)[60]fullerenes show a fast and high photocurrent response in CPL‐detecting devices [17] . Very recently, we reported a high dissymmetry factor of g abs =±0.20 at 710 nm for an open [60]fullerene [18] . Under these circumstances, we thus focused on the synthesis of donor–acceptor type chiral open [60]fullerenes targeted toward a broadband CD activity up to NIR region, in which the effective orbital hybridization with the donor units potentially renders low‐energy transitions electric dipole‐allowed [19, 20] .…”
Section: Introductionmentioning
confidence: 73%
“…Recently, we found that the reaction with nucleophiles such as phosphines results in the formation of zwitterionic open [60]fullerenes showing charge‐transfer transitions with considerably high oscillator strengths at the NIR region [21] . Herein, we used an acyclic diaminocarbene (:C(NMe 2 ) 2 ) as a nucleophile to obtain carbene adduct [22] 2 a while [60]fullerene substrate 1 a is a recently‐disclosed excellent chiral chromophore [18] (Figure 2a). In the presence of tetrakis(dimethylamino)ethylene (TDAE) as a carbene precursor, [23a] 1 a was therefore heated in o ‐dichlorobenzene (ODCB) at 180 °C for 15 min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, as far as chiroptical properties of helical NGs are concerned, there is still large room for improvement. For instance, the g abs value of most chiral NGs stays in the range of 10 –3 , with limited examples approaching 10 –2 . Considering that carbon materials such as chiral open-[60]­fullerene with giant dissymmetry factors, up to 10 –1 , has been achieved, there is no reason to be satisfied with the state-of-the-art chiroptical properties that synthetic helical NGs have displayed.…”
Section: Summary and Outlookmentioning
confidence: 99%